Pembentukan Pustaka Genom, Resekuensing, dan Identifikasi SNP Berdasarkan Sekuen Genom Total Genotipe Kedelai Indonesia - I Made Tasma; Dani Satyawan; Habib Rijzaani (Jurnal AgroBiogen, 2015)
Resequencing of the soybean genome facilitates SNP marker discoveries useful for supporting the national soybean breedingprograms. The objectives of the present study were to construct soybean genomic libraries, to resequence the whole genome offive Indonesian soybean genotypes, and to identify SNPs based on the resequence data. The studies consisted of genomiclibrary construction and quality analysis, resequencing the whole-genome of five soybean genotypes, and genome-wide SNPidentification based on alignment of the resequence data with reference sequence, Williams 82. The five Indonesian soybeangenotypes were Tambora, Grobogan, B3293, Malabar, and Davros. The results showed that soybean genomic library wassuccessfully constructed having the size of 400 bp with library concentrations range from 21.2–64.5 ng/μl. Resequencing of thelibraries resulted in 50.1 x 109 bp total genomic sequence. The quality of genomic library and sequence data resulted from thisstudy was high as indicated by Q score of 88.6% with low sequencing error of only 0.97%. Bioinformatic analysis resulted in atotal of 2,597,286 SNPs, 257,598 insertions, and 202,157 deletions. Of the total SNPs identified, only 95,207 SNPs (2.15%) werelocated within exons. Among those, 49,926 SNPs caused missense mutation and 1,535 SNPs caused nonsense mutation. SNPsresulted from this study upon verification will be very useful for genome-wide SNP chip development of the soybean genome toaccelerate breeding program of the soybean.